Emergence of circulating influenza A H3N2 viruses with genetic drift in the matrix gene: be alert of false‐negative test results. Issue 10 (10th August 2022) - Jørgensen, Rikke Lind; Lerche, Christian Johann; Pedersen, Martin Schou; Kirkby, Nikolai Soren; Botnen, Amanda Bolt; Trebbien, Ramona; Nilsson‐Møller, Stephen; Pinholt, Mette; Nielsen, Alex Christian Yde; Westh, Henrik; Lisby, Jan Gorm; Schneider, Uffe Vest
Abstract : In March 2022, we observed samples with a negative fluorescent signal (60.5%, n = 43) for the influenza A matrix gene and a stronger positive signal for subtype A(H3N2). Forty‐three samples were positive in InfA (H3N2) (mean Cq 30.9, range 23.9–35.1), and 26 of the 43 samples were negative in InfA matrix (mean Cq 28.0, range 23.2–30.6). Our multiplex test is a laboratory‐developed four‐target, four‐color influenza A reverse‐transcription PCR assay targeting the matrix gene, subtypes A(H3N2) and A(H1N1)pdm09. Several samples were negative when retested on commercial influenza Point‐of‐Care assays. As the matrix gene is a stand‐alone target in most commercial diagnostic assays, we caution against false‐negative subtype A test results.